Water Framework Directive Article 7, The Drinking Water Directive and European Pesticide Regulation: impacts on diffuse pesticide pollution, potable water decision making and catchment management strategy - Dolan, Tom (Cranfield University, 2013)
The European Water Framework Directive (WFD) promotes increased awareness of catchment processes and challenges the established dependence on a ‘treatment-led approach’ for the supply of European Drinking Water Directive (DWD) compliant potable water. In particular, WFD Article 7 promotes a ‘prevention-led approach’ to DWD compliance, based on pollution prevention at source to reduce investment in new treatment. In this context the challenge of preventing diffuse pesticide pollution from agricultural sources is significant because metaldehyde (a molluscide) and to a lesser extent the herbicide clopyralid are, despite current treatment, causing DWD non compliance for drinking water in a number of English catchments. Analysis presented here identifies that a successful transition from a ‘treatment-led’ to a ‘prevention-led’ approach will require collective action from, and shared mutual understanding between, a number of stakeholder groups. However, each of these groups has a unique perspective on WFD Article 7 and other elements of the currently uncoordinated legal and voluntary framework for diffuse pesticide pollution prevention. A toolbox of intervention options and a set of criteria to evaluate current catchment management actions are proposed to help the WFD competent authority facilitate WFD Article 7 compliance.Water suppliers need to improve their understanding of the reasons for pesticide use. Through consultation with pesticide agronomists, important drivers of pesticide use, a hierarchy of adaptation options available if a particular pesticide is restricted and key messages for catchment managers and regulators were identified. Based on this foundation a classification system to inform and prioritise water sector decision making for investment in catchment management was developed.Additionally, analysis presented here demonstrates that the DWD standard for pesticides, which determines the level of catchment management required for WFD Article 7 compliance, is not itself consistent with European environmental policy principles, particularly the precautionary principle, and needs to be reviewed.